The Relationship between Health and Schooling: What's New? - Michael Grossman (Institute for the Study of Labor (IZA), 2015)
Many studies suggest that years of formal schooling completed is the most important correlate of good health. There is much less consensus as to whether this correlation reflects causality from more schooling to better health. The relationship may be traced in part to reverse causality and may also reflect "omitted third variables" that cause health and schooling to vary in the same direction. The past five years (2010-2014) have witnessed the development of a large literature focusing on the issue just raised. I deal with that literature and what can be learned from it in this paper. I conclude that there is enough conflicting evidence in the studies that I have reviewed to warrant more research on the question of whether more schooling does in fact cause better health outcomes.
Keywords: I10; I20; 330; efficiency; causality; health; schooling; time preference